2021
DOI: 10.1177/00034894211014786
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Head and Neck Tumors Associated with Li-Fraumeni Syndrome

Abstract: Introduction: Cancer predisposition syndromes are germline pathogenic variants in genes that greatly raise the risk of developing neoplastic diseases. One of the most well-known is Li-Fraumeni syndrome (LFS), which is due to pathogenic variants in the TP53 gene. Children with LFS have higher risks for multiple malignancies before adulthood, often with rare and aggressive subtypes. Objective: To examine head and neck manifestations of LFS in children treated at a tertiary children’s hospital over a 20-year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Furthermore, Sinclair et al reported the case of a 15-year-old female with Li–Fraumeni syndrome who developed a perineal mass, which was diagnosed as myxoid pleomorphic liposarcoma [ 63 ]. A retrospective review of malignancies encountered in children with Li–Fraumeni children has been carried out by Rodriguez et al and included 20 children within a cohort of patients diagnosed with this condition [ 64 ]. Researchers reveal that 6 out of 27 malignancies reported in the analyzed group were sarcomas of the head and neck and were all demonstrated as rare entities—rhabdomyosarcoma, synovial sarcoma, and myxoid pleomorphic sarcoma [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Sinclair et al reported the case of a 15-year-old female with Li–Fraumeni syndrome who developed a perineal mass, which was diagnosed as myxoid pleomorphic liposarcoma [ 63 ]. A retrospective review of malignancies encountered in children with Li–Fraumeni children has been carried out by Rodriguez et al and included 20 children within a cohort of patients diagnosed with this condition [ 64 ]. Researchers reveal that 6 out of 27 malignancies reported in the analyzed group were sarcomas of the head and neck and were all demonstrated as rare entities—rhabdomyosarcoma, synovial sarcoma, and myxoid pleomorphic sarcoma [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective review of malignancies encountered in children with Li–Fraumeni children has been carried out by Rodriguez et al and included 20 children within a cohort of patients diagnosed with this condition [ 64 ]. Researchers reveal that 6 out of 27 malignancies reported in the analyzed group were sarcomas of the head and neck and were all demonstrated as rare entities—rhabdomyosarcoma, synovial sarcoma, and myxoid pleomorphic sarcoma [ 64 ]. The study identifies a propensity for head and neck involvement of tumors associated with Li–Fraumeni syndrome and recommends a multidisciplinary care team surveilling the affected patients [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Typical sarcomas in LFS occur specific to various age groups such as rhabdomyosarcoma in childhood, osteosarcoma in the second decade, and leiomyosarcomas and liposarcomas in adulthood. 8 So far, there are reports of four cases of pleomorphic myxoid liposarcoma occurring in patients with LFS [9][10][11][12] (Table S3). Definitive treatment of pleomorphic myxoid liposarcoma is wide local excision followed by adjuvant radiation.…”
mentioning
confidence: 99%